2009
DOI: 10.1093/carcin/bgp069
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of several phytochemicals and their derivatives on murine keratinocytes in vitro and in vivo: implications for skin cancer prevention

Abstract: The purpose of our study was to investigate in vitro the potential cancer preventive properties of several phytochemicals, i.e. grape seed extract (GSE), resveratrol (RES), ursolic acid (URA), ellagic acid (ELA), lycopene and N-acetyl-L-cysteine (NAC) to define the mechanisms by which these compounds may inhibit murine skin carcinogenesis. We measured quenching of peroxyl, superoxide and hydroxyl radicals by these phytochemicals. We also used adenosine triphosphate (ATP) bioluminescence, Caspase-Glo 3/7 and P4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 52 publications
2
36
0
1
Order By: Relevance
“…8), thus rendering cancer cells more sensitive to the cytotoxic activities of TRAIL. Considering that UA by itself is highly safe and exhibits anticancer activities against a wide variety of tumors in vitro (12,13,18) and in vivo (22,63), its potential use in combination with TRAIL should be explored. Further studies in animals are needed to investigate the anticancer potential of UA in combination with TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…8), thus rendering cancer cells more sensitive to the cytotoxic activities of TRAIL. Considering that UA by itself is highly safe and exhibits anticancer activities against a wide variety of tumors in vitro (12,13,18) and in vivo (22,63), its potential use in combination with TRAIL should be explored. Further studies in animals are needed to investigate the anticancer potential of UA in combination with TRAIL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that UA is effective against various types of cancer both in vitro and in vivo. 16,17 Purported mechanisms include cell cycle arrest and apoptosis induction through inhibition of AKT, 18 STAT3, 19 NFKB1 20 and activation of MAPK8/9/10 21 or TP53 22 signaling pathways. However, the role of ER stress response in UA-induced apoptosis has not been addressed.…”
Section: Autophagy-dependent Eif2ak3 Activation Compromises Ursolic Amentioning
confidence: 99%
“…It has been shown that UA is effective against various types of cancer both in vitro and in vivo. 11,12 The induction of G1 cell cycle arrest and apoptosis by UA has been suggested to contribute to its anti-cancer activities. [13][14][15][16] Previous studies have shown that induction of G1 arrest and apoptosis by UA is associated with up-regulation of cyclin-dependent kinase inhibitor (CDKI) protein p21Cip1 in multiple types of cancer cells.…”
mentioning
confidence: 99%